Conservation and Utilization Rules of the Sula Flowering Walik (Ptilinopus melanosphila) in Local Communities as a Basis for Ex-Situ Conservation - fatmona, Sariffudin; Lestari, Sri; Utami, Sri (Agrikan Jurnal Agribisnis Perikanan, 2024)
This research aims to determine the public understanding and awareness of conservation principles and the government's role in using the Kembang Walik Sula bird. This research was carried out using a census method on Walik Kembang Sula bird breeders and catchers with 30 respondents in three sample villages in the Sula Islands Regency. The research results show that consumption and hobby factors influence community participation in breeding. Community participation in Walik Kembang Sula conservation efforts is still low, influenced by the community's low understanding and awareness of conservation principles and the government's not-yet-optimal role. To maintain the Walik Sula bird population, the government should make a breakthrough that triggers community involvement by creating jobs in the form of opening markets in the culinary sector by using Walik Sula meat as a specialty food and culinary tourism destination, by encouraging ex-situ conservation.